Penerapan Metode Ceramah melalui Media Proyector LCD dalam Pembelajaran SKI Kelas VIII MTsS Al-Islamiyah - Haidir Haidir; Nirwana Anas; Wahyu Sakban; Three Wulan Ramdhani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Passive learning is learning where students have no curiosity, no questions and no interest in the results. The point is that there is no response from students. While active learning is learning where students have the desire to know more by asking and answering questions, needing information for problem solving, and investigating ways to do their work. In the research process, researchers found that Islamic Cultural History (SKI) subject teachers who initially only used the lecture method without being supported by learning media innovated using LCD projector media in the learning process. Therefore, through the results of this study, the researchers tried to analyze how the results of using the lecture method supported by using LCD projector media in learning Islamic Cultural History (SKI) in class VIII Madrasah Tsanawiyah Al-Islamiyah.